1983
DOI: 10.1111/j.1745-4557.1983.tb00756.x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Minced Sucker Flesh

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Usually, the patties prepared using corn flour gave higher cooking yield than those prepared using boiled potato. Dawood et al (1983) made similar observation that the addition of cornmeal and soy protein in combination with sodium chloride improved cooking yield of fish sausages developed from freshwater suckers. Cooking yield (85.1-93.5%) of the L. rohita patties (Sehgal et al 2008) was higher than that of the carp patties.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…Usually, the patties prepared using corn flour gave higher cooking yield than those prepared using boiled potato. Dawood et al (1983) made similar observation that the addition of cornmeal and soy protein in combination with sodium chloride improved cooking yield of fish sausages developed from freshwater suckers. Cooking yield (85.1-93.5%) of the L. rohita patties (Sehgal et al 2008) was higher than that of the carp patties.…”
mentioning
confidence: 56%
“…Gopakumar (1997), and Lipincott and Lee (1983) reported that the starches of potato having high amylopectin content gave cohesive gels as compared to Values with different superscripts in a row for each parameter differ significantly (p≤0.01) P boiled potato, C corn flour cornstarch (having low amylopectin content), which increased rigidity and firmness of gels and thus gave better firmness/texture to the finished product. Dawood et al (1983) also observed that addition of cornmeal and soy protein in combination with sodium chloride improved texture of fish sausage. Chidanandaiah and Keshri (2007) recorded an increase in the sensory score for crispness and adherence of batter of buffalo meat patties coated with batter mix prepared from corn flour (either alone or in combination with Bengal gram flour).…”
mentioning
confidence: 80%
“…Fish sausage may contain land-based animal fat sources as in the case of rainbow trout sausage formulated with 7.5% beef fat (Dincer and Cakli 2010), catfish sausage formulated with variable contents of pork fat (Chuapoehuk et al 2001), and hake sausages developed using beef and pork trim with lipid contents that ranged from 23 to 25% (Park et al 1978). Nonetheless, majority of fish sausage formulations reported in the scientific literature do not contain land-based animal fat sources (Daley et al 1978;Dawood et al 1983;Yin and Jiang 2001;Rahman et al 2007;Moola et al 2008;Sachindra and Mahendrakar 2010;Umesha Bhatta et al 2012;Klanicova et al 2013). Generally, the lipid contents of fish sausages without land-based animal fat ingredients tend to be lower as noted for sausages made from crimson snapper (5.5%; Al-Bulushi et al 2011), croacker (4.96%; Hedge et al 1990), catfish with 3% fish oil (4.5%; Chuapoehuk et al 2001), saithe (4.6%; Nordvi et al 2007), rohu (7.08%; Sini et al 2008) and unwashed minced Nile tilapia muscle (6.…”
Section: Proximate Composition and Salt Content Analysesmentioning
confidence: 99%
“…), Spanish mackerel ( Scomberomorous maculatus ; Lee and Toledo ), freshwater sucker fish (Catostamidae family; Dawood et al . ), channel catfish ( Ictalurus punctatus ; Medeiros et al . ); Atlantic cod ( Gadus morhua ; Hastings ), crocker ( Jhonius spp; Hedge et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation